Preventive and recuperative oral health care for pregnant women in Peru - Vicuña-Huaqui, Luis Antonio Vicuña-Huaqui (2023)
During pregnancy, physiological changes increase the risk of oral pathologies, such as periodontitis, gingivitis, caries lesions, dental erosion and pyogenic granulomas. Therefore, it is essential to provide timely care to maintain the oral health of pregnant women. Objective: To describe the characteristics of preventive and recovery oral health care in pregnant women in public health centers in Peru. Materials and methods: Observational, descriptive, cross-sectional study based on secondary data on odontostomatology care during 2017. The variables trimester of pregnancy, maternal age range, preventive and recuperative procedure, region, and treatment condition were analyzed. The data were analyzed in the RStudio program, and the results were presented in tables with relative and absolute frequencies. Results: 35,523 preventive procedures were performed, 37.3% in the second trimester; 21.8% corresponded to stomatological examination; and 21.7% to oral hygiene instruction; 69.8% in the 18-29-year age group; and 15.5% in the Junin region. There were 4265 recovery procedures, 39.0 % in the second trimester; 53.1 % corresponded to dental scaling and 18.9 % to stomatological consultation, 61.7 % in the 18-29-year age group, and 16.25 % in the Huánuco region. Conclusion: A more significant number of pregnant women accessed preventive care compared to access to oral health recovery procedures, and the dropout rate was predominant in both cases. Both procedures were performed more frequently in high Andean regions and young adult mothers during the second trimester.